THE ROLE OF WOMEN IN THE EDUCATION SYSTEM IN TURKISTAN IN THE 19TH–20TH CENTURIES - Nuriddinova Aziza Ilhomovna (World Scientific Research Journal, 2026)
Annotation: This article examines the changing position of women within the education system of Turkistan from the traditional order of the nineteenth century through the reformist Jadid movement of the late nineteenth and early twentieth centuries to the mass literacy campaigns of the early Soviet period. Using a qualitative historical-comparative method based on Jadid periodicals, secondary historical scholarship, and studies of Soviet policy in Central Asia, the article identifies three successive phases in the development of women’s education: informal religious instruction confined to the household, Jadid-led reform aimed at winning public acceptance for girls’ schooling, and Soviet state compulsion, most visibly embodied in the 1927 Hujum campaign. The findings show that each phase built upon, and in some respects erased, the one before it, and that the near-universal female literacy characteristic of Uzbekistan today rests on this layered and at times contradictory history. The article concludes that understanding this trajectory is essential to interpreting the present-day educational and social landscape of Central Asia.